Aplikasi Cendawan Entomopatogen Beauveria bassiana yang Ditambahkan Silika Gel untuk Mengendalikan Hama Tanaman Tomat - Siti Maulida; Muhammad Indar Pramudi pramudi (www.ulm.ac.id, 2026)
This study aims to evaluate the effectiveness of the entomopathogenic fungus Beauveria bassiana formulated with silica gel in controlling leaf pests on tomato plants (Solanum lycopersicum). The research was carried out using a one-factor Completely Randomized Design (CRD) with nine treatments and three replications. The parameters observed include the number of pest populations and the level of attack intensity. Based on the results of observations, treatment C, namely B. bassiana, with the addition of 7% silica gel and stored for five days showed the highest effectiveness in reducing pest populations and attack intensity, with the lowest attack average of 0.92. The addition of silica gel was proven to be able to increase the stability of the formulation and the effectiveness of B. bassiana infections, although statistically it did not always show a significant difference compared to treatment without silica. The main type of pest that has been successfully controlled is aphids (Myzus persicae). This formulation shows great potential as an environmentally friendly biological control alternative in tomato cultivation systems